2021
DOI: 10.1021/acsfoodscitech.1c00012
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach for Producing Processed Cheese Fortified with Date Syrup

Abstract: The current study focuses on an innovative approach to developing novel processed cheese that has health benefits by adding date syrup (15, 20, and 25%) as a suitable natural material with a distinct flavor of sugar, in addition to its nutritional and functional components. The results showed that the resultant date-syrup-processed cheese (DSPC) was more acceptable (smoother and sweeter) and had improved physico-chemical and rheological properties. There is a gradual increase in the K, total carbohydrate, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
5
7
0
Order By: Relevance
“…There were slight changes in potassium content during storage, with a general irregular fluctuation. The findings of this study are in agreement with previous reports indicating that the addition of dates improved the potassium content of fermented dairy products [ 33 , 34 , 38 , 49 ]. In addition, the amount of potassium in this study was comparable with amounts (921–1337 mg/kg) reported in yogurt fortified with fruit [ 54 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…There were slight changes in potassium content during storage, with a general irregular fluctuation. The findings of this study are in agreement with previous reports indicating that the addition of dates improved the potassium content of fermented dairy products [ 33 , 34 , 38 , 49 ]. In addition, the amount of potassium in this study was comparable with amounts (921–1337 mg/kg) reported in yogurt fortified with fruit [ 54 ].…”
Section: Resultssupporting
confidence: 93%
“…Similarly, previous a report indicated that the addition of 2% dibs affected the fat and acidity levels of yogurt in a negative manner [ 33 ]. In addition, a reduction in fat content was observed following the addition of dates to fermented milk beverage [ 35 , 36 ] and the addition of date syrup to processed cheese [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that different amounts of protein were introduced into the PC with these additives (maximally approximately 0.18 g/100 g of cheese in the case of 3% spirulina addition), which was, however, much smaller than the "loss" of protein content resulting from the reduction in the amount of rennet cheese in the PC formula. Our data exhibit the same trend as that found in the studies of Alqahtani et al [38], El-Loly et al [39], and Aly et al [40], which used date fruit seeds, date syrup, and bulgur, respectively.…”
Section: Chemical and Physicochemical Characterization Of Processed C...supporting
confidence: 91%
“…Some other nutritionally vital constituents are found in date syrup, including dietary fiber, vitamins C and B-complex, and antioxidants such as polyphenols, flavonoids, and carotenoids. Its health benefits are diverse in its effects on body metabolism, such as antimicrobial, antimutagenic, immunostimulant, hepatoprotective, nephroprotective, gastroprotective and anti-hyperlipidemic properties . At the research level and commercial level, date syrup has been fortified and added in various food products such as functional yogurt, dough and bread, fermented milk drinks, processed cheese, rabri milk drink, probiotic dairy desserts and different backed goods and drizzled over ice cream, oatmeal, yogurt, French toast, pancakes, or even savory bites, such as a grilled cheese sandwich. In Arabic countries, date syrup in an essential cooking ingredients in various native dishes and added to improve the flavor of poultry, meat, fish, vegetables, pasta and rice. It is also drizzled over cheesecakes, cream cakes, toast, croissants, bagels, pancakes, sorbets, crepes and shakes .…”
Section: Vegan Sweetenersmentioning
confidence: 99%